Pengaruh Faktor Kontekstual Terhadap Kegunaan Earnings dan Arus Kas Operasi dalam Menjelaskan Return Saham - Shinta Rahma Diana; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to examine the incremental information content of earnings and cash flows from operation using a research methodology which explicitly incorporates contextual factors (earnings permanence, growth and firm size) that may add to an understanding of the relative usefulness of cash flows and earnings in explaining stock returns. As much as 516 manufacturing firms listed in the Jakarta Stock Exchange (BEJ) were taken as a sample using a purposive sampling method. This study uses the current level of earnings (operating cash flows) and the change in earnings (operating cash flows).The results show that, for change variable, the earnings response coefficient is related to earnings permanence and growth and that the cash flow response coefficient is related to firm size. For change and level variable, the earnings response coefficient is related to earnings permanence and growth and that the cash flows response coefficient is related to earnings permanence, growth and firm size. This study also indicates that cash flows from operations is important in explaining security returns in the following year and show that both earnings changes and levels have explanatory power when they are included simultaneously in a regression model of abnormal returns on earnings. This evidence is consistent with Easton and Haris (1991).